N-Acetil-B-D-glucosaminidase (NAG): padronização de ensaio espectrogométrico automático em urina de cães - Luiz Eduardo de Souza Tassini (2015)
The determination of renal injury, especially through the assessment of the activity of urinary enzymes, is an important tool for the veterinary doctor, especially by its precocity in relation to methods of evaluation of renal function, which are considered to happen late, since the installation of injury precedes the change in the function. In this study was performed the standardization of reagents, determination of a reference value (with and without correction for urine density) and assessment of stability - in different temperature ranges - the enzyme NAG (N-acetyl-beta-D-glucosaminidase) for dogs (male and female), healthy individuals of different age groups. For the standardization of reagents for evaluation of urinary activity of NAG in dogs, the enzyme showed optimal pH and concentration of substrate similar to those used in commercial kits for evaluation of the activity of this enzyme in humans. The automation of the technique for the assessment of urinary NAG activity in humans, for healthy dogs in different age groups, has proved to be effective. By means of statistical analysis, it was observed that NAG presents a positive correlation with the age and urine density of the animal. Once applied the correction formula for urinary specific density of 1.025, the average confidence interval of urinary activity of NAG was shorter than when there was no correction and statistically it was concluded that the activity of urinary NAG, with correction of urinary density is more accurate. In order To evaluate the stability of urinary enzyme, were analyzed three methods of conservation of urine in temperatures of -20 C, 2-8C and 20-30C, with retention times of 24, 48, 72 hours and 7 and 15 days. It was concluded that the storage method of urine samples at a temperature of 2-8C is a reliable method of storage for up to 7 days, without any statistical changes in the values found in the analyzes of the samples. The methods of conservation in temperatures of -20 C and at temperatures of 20-30C proved to be unsuitable for conservation of urine samples for later evaluation of urinary activity of NAG due to statistical differences in average values over time.